The Relationship Parents’ Attention and Motivation Learning Santri Taman Pendidikan Al-Qur’an - Kesy Wenisa; Syur'aini Syur'aini (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2020)
This study aims to describe the attention of parents to students at TPQ Al-muasyarah Jorong Hulu Banda, Malalak District. This type of research is a quantitative descriptive study. The population in this study were 75 students of TPQ Al-muasyarah Jorong Hulu Banda, Malalak District. The sample in this study amounted to 38 (50%) people using the proportionate stratified random sampling technique. The data collection techniques used were questionnaires and documentation. Quantitative data analysis used descriptive analysis with the help of SPSS software. The results of this study indicate 1) The attention of parents to students is classified as high enough, 2) The motivation to learn students is classified as high. Research suggestions are: 1) Parents should be able to provide learning motivation to children in order to improve understanding and learning achievement of students, 2) It is hoped that other researchers can look for other variables that affect students' learning motivation.Keywords: Al-Qur'an Education Park, Parents' Attention, Learning Motivation